Semantic Analysis Of Islamic Values In Contemporary Dakwah Discourse On Social Media - Ahmad Rijali (Journal of Innovative and Creativity (Joecy), 2026)
This study analyzes Islamic values in contemporary da'wah discourse on social media through a semantic approach using Roland Barthes' semiotic framework. The digital era has fundamentally transformed the landscape of da'wah communication, where social media platforms have become primary spaces for disseminating Islamic messages. This research aims to identify and describe the meanings of Islamic values constructed in digital da'wah content and analyze the semantic strategies employed in delivering da'wah messages. The study employs a qualitative approach with semantic analysis as the main framework. Data were obtained from 50 da'wah content pieces on Instagram and Facebook platforms during the 2025-2026 period, selected through purposive sampling. Findings reveal that Islamic values in contemporary da'wah discourse are represented through four dominant patterns: (1) modern religiosity emphasizing visual aesthetics and simplicity, (2) social ethics highlighting humanitarian responsibility, (3) religious organizational identity with reformist orientation, and (4) akhlaq (moral character) as the fundamental foundation of da'wah. These findings indicate that social media functions as a dynamic and adaptive space for constructing Islamic meaning in response to contemporary developments. The research contributes to digital da'wah studies by providing a semantic framework for analyzing religious discourse in digital environments and offers practical recommendations for da'wah practitioners in optimizing social media for Islamic communication.